Malignant mesothelioma due to non-occupational asbestos exposure from the Italian national surveillance system (ReNaM): epidemiology and public health issues. Issue 9 (4th June 2015) - Marinaccio, Alessandro; Binazzi, Alessandra; Bonafede, Michela; Corfiati, Marisa; Di Marzio, Davide; Scarselli, Alberto; Verardo, Marina; Mirabelli, Dario; Gennaro, Valerio; Mensi, Carolina; Schallemberg, Gert; Merler, Enzo; et al.
Abstract : Introduction: Italy produced and imported a large amount of raw asbestos, up to the ban in 1992, with a peak in the period between 1976 and 1980 at about 160 000 tons/year. The National Register of Mesotheliomas (ReNaM, "Registro Nazionale dei Mesoteliomi" in Italian), a surveillance system of mesothelioma incidence, has been active since 2002, operating through a regional structure. Methods: The Operating Regional Center (COR) actively researches cases and defines asbestos exposure on the basis of national guidelines. Diagnostic, demographic and exposure characteristics of non-occupationally exposed cases are analysed and described with respect to occupationally exposed cases. Results: Standardised incidence rates for pleural mesothelioma in 2008 were 3.84 (per 100 000) for men and 1.45 for women, respectively. Among the 15 845 mesothelioma cases registered between 1993 and 2008, exposure to asbestos fibres was investigated for 12 065 individuals (76.1%), identifying 530 (4.4%) with familial exposure (they lived with an occupationally exposed cohabitant), 514 (4.3%) with environmental exposure to asbestos (they lived near sources of asbestos pollution and were never occupationally exposed) and 188 (1.6%) exposed through hobby-related or other leisure activities. Clusters of cases due to environmental exposure are mainly related to the presence of asbestos-cement industry plants (Casale Monferrato, Broni, Bari), to shipbuilding and repair activities (Monfalcone, Trieste, La Spezia, Genova) and soil contamination (Biancavilla in Sicily). Conclusions: Asbestos pollution outside the workplace contributes significantly to the burden of asbestos-related diseases, suggesting the need to prevent exposures and to discuss how to deal with compensation rights for malignant mesothelioma cases induced by non-occupational exposure to asbestos.